Pengaruh variasi layout runner dan melt temperature terhadap fill time dan defect pada proses injection molding sikat gigi - Arif Budi Wicaksono; Agus Surachman (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
This research aims to determine the influence of layout variations, runner system and melt temperature to the characteristics of radial and grid layouts. The runner system is varied with two types of runners that are grids with H and Block runners, Radial with Star and Block. Melt temperature is variated at 230oC, 240oC and 250oC. The best results are obtained using grid layout with block runner system and melt temperature at 230oC with fill time, defects and optimum quality prediction. Optimum mold unit design with grid layout and block runner system with dimensions of 550 x 300 mm with clamping force of 686.72 kN. One of the machines that can be used SUN-110 with clamp fore 1000 kN.